29. ROLE OF AGE AND CNS MYELOID CELLS ON BREAST CANCER BRAIN METASTASIS. (4th August 2020) - Lai Wu, Alex Man; Gossa, Selamawit; Samala, Ramakrishna; Chung, Monika; Gril, Brunilde; Yang, Howard; Thorsheim, Helen; Tran, Andy; Wei, Debbie; Isanogle, Kristine; Yang, Yuan; Dolan, Emma; et al.
Abstract: Women diagnosed with breast cancer at a younger age (typically defined as < 40 years old) often have a poorer prognosis and an increased risk of brain metastasis compared to their older counterparts. Multivariate analyses accounting for differences in tumor characteristics have shown that age is an independent predictor of worse outcome. We therefore hypothesized that rather than intrinsic tumor properties, extrinsic microenvironmental factors contribute to age-related differences in aggressiveness. The effect of age was examined by injecting brain-selected breast cancer cells into young (2 – 6 months) and older (>12 months) mice. In four brain metastasis models examined, young mice developed 2- to 16-fold (p < 0.05) more brain metastases compared to older mice. The effect of age was not observed in mouse breast cancer models that metastasize to liver and lungs, suggesting that this is an organ-specific phenomenon. Flow cytometry-based immune-profiling of mouse brains showed that T-cells (CD4+, CD8+, and FOXP3+CD25+ regulatory T-cells), monocytes and neutrophils were elevated in brains with metastases, but the abundance of these populations did not vary dramatically with age. Furthermore, antibody-based depletion of T-cells, monocytes and neutrophils did not significantly alter brain metastasis development. Microglia, which are resident CNS myeloid cells, were 1.5-fold more abundant in young brains compared to older brains. Depletion of CNS myeloid cells using the colony stimulating factor-1-receptor inhibitor PLX3397 reduced brain metastatic tumor burden in young mice by 2.1-fold (p < 0.001). Importantly, loss of CNS myeloid cells/microglia, which are normally more activated in aged mice and thus may protect the older brain against metastasis, did not augment brain metastasis formation in older mice. These results suggest that the younger brain is more permissive for breast cancer metastasis and that targeting resident CNS myeloid cells may be an effective strategy to prevent brain metastasis development in younger patients.